2020
DOI: 10.1186/s40695-020-00053-0
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of common chronic conditions to midlife physical function decline: The Study of Women’s Health Across the Nation

Abstract: Background: Chronic conditions are associated with worse physical function and commonly develop during midlife. We tested whether the presence of 8 chronic conditions, or the development of these conditions, is associated with declines in physical function among midlife women as they transition into early late life. Methods: Participants (N = 2283) were from the Study of Women's Health Across the Nation. Physical function was assessed at 8 visits starting at the study's fourth clinic visit in 2000/2001 through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Development of an incident chronic medical condition was associated with an additional 1.9% poorer score and a 0.33% yearly rate of decline per condition [ 96 ]. As noted above, Black were women more likely than White women to start the study with prevalent, and then to develop, incident hypertension, diabetes mellitus, MetS, and OA [ 97 ]. Additionally, at the 12 th follow-up visit the Michigan site administered the World Health Organization Disability Assessment Schedule (WHO-DAS): Black women were twice as likely as White women to report moderate to extreme global disability [ 98 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of an incident chronic medical condition was associated with an additional 1.9% poorer score and a 0.33% yearly rate of decline per condition [ 96 ]. As noted above, Black were women more likely than White women to start the study with prevalent, and then to develop, incident hypertension, diabetes mellitus, MetS, and OA [ 97 ]. Additionally, at the 12 th follow-up visit the Michigan site administered the World Health Organization Disability Assessment Schedule (WHO-DAS): Black women were twice as likely as White women to report moderate to extreme global disability [ 98 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chronic medical conditions negatively influence physical function and performance; Black-White disparities in the prevalence and incidence of major diseases account for some of the observed disparity in physical performance and physical disability [95][96][97][98]. In the full SWAN sample, each additional chronic medical condition present at baseline was associated with a 4.0% poorer self-reported baseline physical functioning score; each additional baseline medical condition also increased the score's annual rate of decline by 0.20% yearly.…”
Section: Self-reported Physical Function and Measured Physical Perfor...mentioning
confidence: 94%
“…We investigated associations between PF and CVD risk, but PF is also known to decline as a result of CVD (Keeney et al, 2019; Levine et al, 2014). Previous work in SWAN demonstrated that women experience declines in PF in conjunction with the development of new chronic conditions, (Lange-Maia et al, 2020b) with incident stroke being associated with a 12% subsequent drop in PF, and an accelerated decline in PF concurrent with incident heart disease (Lange-Maia et al, 2020a). From a prevention standpoint, there are shared intervention targets that are related to PF improvement as well as CVD risk reduction and diabetes prevention and control.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 3 , 4 Furthermore, evidence suggests that these limitations or decreases in physical health and function are associated with chronic conditions that develop before or during midlife. 5 However, other work has shown the highly dynamic nature of functional status during midlife, 6 demonstrating that some women may improve their physical health and functioning during this time. 7 , 8 …”
Section: Introductionmentioning
confidence: 99%